Pengaruh Modal Krja, Persediaan dan Penjualan Terhadap Laba Bersih (Pada Perusahaan Semen yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2016-2024) - Dapit, Dapit; Sjarif, Devyanthi; Sajekti, Tjipto (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to examine the influence of working capital, inventory, and sales on net profit in cement companies listed on the Indonesia Stock Exchange (IDX) during the 2016–2024 period. Employing a quantitative approach with associative descriptive analysis, this research uses secondary data sourced from financial reports. The classical assumption tests—normality, multicollinearity, heteroscedasticity, and autocorrelation—were conducted before performing multiple linear regression analysis. The results reveal that working capital and sales have a significant and positive effect on net profit, while inventory does not show a statistically significant influence. Simultaneously, all independent variables collectively have a significant impact on net profit. These findings emphasize the importance of efficient working capital management and sales performance in enhancing profitability. This study contributes to managerial decision-making by providing empirical evidence on financial factors that drive earnings performance in the cement industry